Exploring the Potentials of Unplugged Activities: Developing Computational Thinking in Teacher Education - Rehder , Mads Middelboe; Jensen, Jesper Juellund; Møller, Thilde Emilie; Schrøder, Vibeke (Nordic Journal of Comparative and International Education (NJCIE), 2024)
This paper explores the use of unplugged activities as a pedagogical approach for teaching computational thinking (CT) to student teachers at a Danish university college in the subject technology comprehension. Through an analysis of three cases—a toothbrushing routine, a political profiling quiz, and an interactive story creation—the study examines students’ learning experiences and engagement with CT concepts and practices. The paper employs a methodological approach rooted in participatory observation and visual ethnography. Data collection includes video recordings, audio recordings, post-class interviews, and artefacts created by the students. The analysis reveals possibilities as well as challenges experienced by students in their involvement in computational thinking activities, including algorithms, decomposition, and abstraction. These findings contest the oversimplified classification of activities as either 'plugged' or 'unplugged', suggesting that alternative factors hold more substantial importance. Subsequently, the paper explores the roles of self-efficacy and ‘be-greifbarkeit’ in students' learning processes, thereby elucidating how students' motivation and learning expectations, in conjunction with their tangible experiences and conceptual understandings, influence the development of their computational thinking competencies. In conclusion, the study provides valuable insights for teacher educators, emphasising the need to consider the perceived complexity of the activity, including the students’ prerequisites for engaging with plugged and unplugged elements. It highlights the multifaceted nature of plugged and unplugged approaches, offering a nuanced perspective on their impact on students' learning experiences in the field of computational thinking.